UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN PADA MASA PANDEMI COVID-19 DI SEKOLAH DASAR ISLAM DIPONEGORO DAMPIT MALANG - Aimatur Rodifah; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
This study aims to describe the principal’s efforts in improving the quality of learning during the Covid-19 at SD Islam Diponegoro Dampit. This research is qualitative. Data collection techniques with observation, interview and documentation. The subject in this study were the principal and teachers as well. The object of this research in the quality of learning, the principal’s efforts in improving the quality of learning. This analisis data used the Milles and Humberman model, namely data condensations, data presentations, and drawing conclusions. The technique of checkings the validity of the data by using triangulation techniques. The results of the study indicate that the quality of learning at SD Islam Diponegoro Dampit is good, and the efforts made by the principal by guiding and evaluating the learning provided by the teacher during online learning are good.   Kata kunci: Pemimpin, Upaya Kepala Sekolah, Mutu Pembelajaran